Steering simulation performance in patients with obstructive sleep apnoea and matched control subjects. - Juniper, M; Hack, M; George, C; Davies, R; Stradling, JR (2000)
Patients with obstructive pulmonary disease (OSA) have an increased rate of driving accidents, perhaps due to poor vigilance or impaired cognitive skills that influence their driving ability. The authors have assessed whether patients with OSA perform differently to control subjects on a steering simulator which allows the separate assessment of the two visual tasks required for steering a car, immediate positioning on road with reference to the road edges, and assessment of the curve of the oncoming road which allows faster driving. Twelve patients with OSA and 12 control subjects, matched for age, sex and driving experience, performed three 30-min drives with either all the oncoming road visible, only the near part of the road visible, or only the distant part of the road visible. Steering was assessed by measuring the SD around the theoretical perfect path (steering error) and the number of times the driver went "off road". Subjects identified the appearance of target numbers at the four corners of the screen as quickly as possible, thus making the test a divided attention task. Patients with OSA performed significantly less well on the three different road fields as measured by steering error (p<0.001), time to detect the target number (p<0.03), and off road events (p<0.03). The patients appeared to be particularly impaired on the two drives when only part of the road ahead was available to guide steering. This steering simulator, with its more realistic view of the road ahead, identifies impaired performance in patients with obstructive sleep apnoea. In addition it suggests that patients with obstructive sleep apnoea may be more disadvantaged compared to normal subjects when the view of the road ahead is limited (such as in fog).